Dissolved Organic Carbon (DOC) in Ground Ice on Northeastern Tibetan Plateau - Yang, Yuzhong; Guo, Xiaoyan; Wang, Qingfeng; Jin, Huijun; Yun, Hanbo; Wu, Qingbai (Frontiers in Earth Science, 2022)
Ground ice in permafrost stores substantial amounts of organic carbon (OC) that are vulnerable to degradation as dissolved organic carbon (DOC) upon thaw which may perpetuate a permafrost carbon feedback. Such releases will affect carbon cycle and biogeochemistry in permafrost regions, yet little is known to date about the dynamics of DOC and source variability of ground ice in permafrost on the Tibetan Plateau. Here, the high-resolution data of DOC in ground ice (4.8 m in depth) from two sedimentary contrasting permafrost profiles on the Northeastern Tibetan Plateau (NETP) was first presented. We quantified the DOC concentrations (mean: 9.7~21.5mg/L) of ground ice and revealed sizeable-by a factor of 7.0 to 36.0-enrichment of the ground ice relative to the other water elements on the TP. Results indicated remarkable depth differences in the DOC of ground ice, suggestive of diverse sources of DOC and different sequestration processes of DOC into ice during permafrost evolution. Combined with DOC and carbon isotopes (δ13CDOC), we clarified that decomposition of soil organic matter and leaching of DOC from organic layers and surrounding permafrost sediments are the important carbon sources of ground ice. The DOC sequestration of ground ice in the upper layers was related to the active layer hydrology and freeze-thaw cycle. However, the permafrost evolution controlled the decomposition of organic carbon and sequestration of DOC in the deep layers. A conceptual model clearly illustrated the dynamics of DOC in ground ice and suggested a significant impact on the carbon cycle under permafrost thawing on the NETP. The first attempt to explore the DOC in ground ice on the NETP is important and effective for further understanding of carbon cycle and biogeochemical processes under permafrost degradation on the Tibetan Plateau.